2006
DOI: 10.2337/db05-1455
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Insulin Signaling and Increased Apoptosis inCd38-Null Islets

Abstract: ؊/؊ islets were significantly more susceptible to apoptosis compared with islets isolated from littermate controls. This finding correlated with disrupted islet architecture and reduced ␤-cell mass in Cd38 ؊/؊ mice, both in the context of a normal lab diet and a high-fat diet. Nevertheless, we did not find robust differences in glucose homeostasis in vivo or glucose signaling in vitro in Cd38 ؊/؊ mice on the C57BL/6 genetic background, in contrast to previous studies by others of Cd38 knockout mice on the ICR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 68 publications
5
44
0
Order By: Relevance
“…Mouse islets were isolated from 10-to 12-week-old C57BL/6J mice as described [25] and cultured overnight in RPMI 1640 with 10% (vol./vol.) FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse islets were isolated from 10-to 12-week-old C57BL/6J mice as described [25] and cultured overnight in RPMI 1640 with 10% (vol./vol.) FBS.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, insulin has anti-apoptotic as well as enhancing proliferation effects on beta cells of islets (50). To assess whether the feedback-regulating effect on islets beta cells is through transcriptional factor Isl-1, we checked the changes of Isl-1 expression after the cultured NIT cells were treated with insulin, and the results showed that insulin significantly decreased the insulin receptor and Isl-1 gene expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to ALX3, deficiency of other transcription factors that regulate insulin gene expression and beta cell function also leads to increased beta cell apoptosis and impaired islet function [4]. Increased apoptosis in pancreatic islets can lead to decreased beta cell mass to the point of compromising islet cell function [6,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In Alx3-deficient mice we observed altered islet architecture, evidenced by mislocalisation of a number of alpha and delta cells found scattered throughout the islet core (not shown). Defects in islet architecture have often been associated with increased beta cell apoptosis [6,31]. Nonetheless, lack of ALX3 may lead to apoptosis by other mechanisms that are unrelated to GCK production.…”
Section: Discussionmentioning
confidence: 99%